Transcultural negotiations of gender : studies in (be)longing - Bhaduri, Saugata; Mukherjee, Indrani (New Delhi ; Heidelberg ; New York ; Dordrecht ; London : Springer, 2016)
Transcultural Negotiations of Gender probes into how gender is negotiated along the two axes of `belonging' and `longing'- the twin desires of being located within a cultural milieu, while yearning for either what has passed by or what is yet to come.
14.1 Introduction -- 14.2 Storyline -- 14.3 Different Genders, Different Bhavas -- 14.3.1 Sasirekha in Courtship -- 14.3.2 Sasirekha in Protest -- 14.3.3 Sasirekha in Marriage -- 14.4 Conclusion -- References -- 15 The Relevance of Gender in the Narco CorridoNarco Novel -- Abstract -- References -- Part IV Modernity, Technology and (Be)longing -- 16 Tagore's Women Heralding The "New Indian Woman": A Critique of the Women's Question in the Nationalist Discourse -- Abstract -- References -- 17 Manasi to Neera: The Evolution of the Concept of "Muse" in Modern Bengali Poetry -- Abstract
Includes bibliographical references (pages 221-222)
ENH
Trim Education
Keywords: Sex role -- Cross-cultural studies; Gender expression -- Cross-cultural studies; English literature